(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
The concept of Creative Economy has been debated during the last decade in countries with different cultural, social and economic contexts. The creative economy is the cycle that encompasses the creation, production and distribution of products and services that use knowledge, creativity and intellectual assets as the main productive resources of cultural wealth. In Brazil, in 2013, the Ministry of Culture (MinC) created the Observatory of Creative Economy of Brazil (OBEC) with a proposal for coordination of action that was extended throughout the Brazilian society and coordinates the promotion of the public policies of culture, supports citizen action and cultural diversity to strengthen the cultural role of groups and communities, with access to cultural assets. The Federal University of Amazonas, in 2013, in the exercise of its ethical, political and social commitments in the Amazon region, as part of the Brazilian network of the creative economy of the MinC, has organized the Observatory of Creative Economy of the State of Amazonas ( OBEC-AM) whose objective is to map existing studies on production and consumption of the Creative Economy; promote new studies and create an information system and the exchange of experiences, spaces for innovation among producers and development agencies; and train professionals. The result of the work of OBEC-AM is the promotion of interactive actions of dissemination, exchange, information for public policies and structuring of technical actions aimed at creative skills.